INDONESIAâ€™S DEMOCRACY UNDER JOKO â€œJOKOWIâ€ WIDODO LEADERSHIPS: CONSTRUCTING HUMAN RIGHTS IN GLOBALIZATION (2014-2019) - Hendra Manurung (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2017)
On 20 October 2014, Joko “Jokowi: Widodo was inaugurated as 7th Indonesia President in the Parliament House, Senayan, to lead the world biggest Muslim country for 5 (five) years presidency (2014-2019). President Joko Widodo’s record during his first year in office was mixed. His administration signaled it would more actively defend the rights of beleaguered religious minorities, victimized by both Islamist militants, and discriminatory laws, but made few concrete policy changes. He granted clemency in May 2015 to five of Papua’s political prisoners and released another one in October, but at the same time had not freed the approximately 70 (seventy) Papuans and 29 (twenty nine) Ambones which still imprisoned for peaceful advocacy of independence. He announced lifting of decades-old restrictions on foreign media access to Papua, but then did not follow through, allowing senior government officials to effectively defy the new policy without consequences. While in August 2015, Joko Widodo announced that Jakarta will create a reconciliation commission in addressing human rights violations of the past 50 years and still left out the details (1965-2015). This research attempts to describe analytically how Indonesia Human Rights policy affects and providing solution to overcome national human rights issues. Keywords: minorities, discrimination, human rights, national policy, leaderships Abstrak Pada tanggal 20 Oktober 2014, Joko